Optimalisasi Penggunaan Teknologi Artificial Intelligence dalam Proses Pembelajaran Bagi Guru di MGMP Matematika SMA Kabupaten Sigi - Mubarik; Lefrida, Rita; Rochaminah, Sutji; Bakri; Alfisyahra; Nasir, Rahma (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The development of Artificial Intelligence (AI) technology opens up significant opportunities for improving the quality of mathematics learning. However, many high school mathematics teachers are still unfamiliar with the use of AI, particularly the use of the Python programming language as a learning support medium. This community service activity aims to improve the knowledge, understanding, and skills of high school Mathematics MGMP teachers in utilizing Python-based AI technology in the learning process. The implementation method includes a preparatory stage in the form of coordination with partners, observation, and interviews to identify teacher needs, and an implementation stage consisting of two training sessions. The first training phase focused on providing conceptual material regarding AI applications in learning, while the second training phase included practical assistance in creating AI-based learning media using Python. The results of the activity showed an increase in teachers' understanding of AI concepts and practical skills in using Python to develop simple interactive quizzes in mathematics learning. Furthermore, participants demonstrated active and collaborative participation throughout the activity. Thus, this community service activity contributed to improving teachers' technological literacy and encouraging innovation in more interactive mathematics learning. It is recommended that similar activities be carried out continuously with a broader scope of material to optimize the use of AI in learning